ORGANIZATIONAL CHANGES IN THE ENTERPRISE: THE INFLUENCE OF EMPLOYEE REACTION - Smolinets, Igor (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2021)
The pace of organizational change faced by business organizations continues to grow every year. This is the result of progress in the field of information and communication technologies, which increases the democratization and liberalization of the world’s economies. Our study of employee response to organizational change identified three main areas: The first perspective of the study identifies different personality traits of employees as determinants of resistance or support for change. The main approaches and models to the analysis of the influence of individual characteristics (tendencies) on the effectiveness of organizational change are analyzed. For example, it turned out that employees who are afraid of the unknown and tend to be more skeptical about it are more likely to resist. The first direction showed that people with a higher level of self-esteem and self-efficacy are more likely to support any change. The second direction focuses on the relationship between the employee and the organization. Here, scholars have focused on the role of trust in managerial or organizational settings. The last direction concerns the internal communication of change processes, which keeps the organization in the period of organizational change. The role of individual tendencies in the processes of organizational change, psychological factors of perception or resistance to these changes were considered. It was noted that the variables of organizational communication perform two main tasks: first, it serves to transmit information, and secondly, the use of commands as the main links and factors of organizational adaptation. We compared Cotter’s model of urgent change with other models and determined that Luke’s "Seven Steps" model offers a good way to diagnose and understand the current state of the business (before the change), as well as the goal (which is pursued by the change). Therefore, it can significantly help to start the process of change and provide the necessary guidance for success. The effective use of this model depends on whether these steps are implemented.